Progress of 2nd Plan (First Three Years of Achievement) Kashmir - Planning Commission (Planning Commission, 1959)
The Plan in the State has faced various odds during the first three So far as the achievement of targets is concerned the Plan has years of the Second Plan period, much in the same way as difficulties been successfully implemented in most of the sectors. In respect of have been experienced in other parts of the country in the implement the Industrial sector achievement has been successful during the last lesson of the Plan. Foreign exchange difficulties presented a serious of year so far as the drawing up of blue-prints, placing of orders abroad table in the execution of some schemes. Equally serious was the set back and arranging of foreign exchange are concerned. It will be realized given to the Plan by increase in the price level all over the country part that setting up of industrial plants requires a great deal of preliminary clearly in that of food stuffs. Besides these factors which militated against work particularly when there are acute foreign exchange difficulties, a smooth working of our schemes was the additional harm that came Since the Programme has received momentum in the shape of important from the flood of 1957-58. Preliminaries having been finalized it is hoped that substantial results will be available in this sector by the end of the 2nd Plan. Similarly It is in the light of these difficulties, that we must look at the our difficulties in the field of Irrigation arise from the fact that invest- implementation of various development works. The credit for the progress ration and surveys of projects have to be completed before their execution achieved despite these and other difficulties goes to the public, who can be taken up. Notwithstanding this handicap in this field of our extended their valuable co-operation in all spheres. Work also good results have been achieved. Irrigation schemes with a capacity for irrigating about 19 thousand acres of land have been the following table explains the progress made by the Plan in completed during 1958-59 as against about 7 thousand acres of land financial terms. It will be seen that expenditure incurred during the in the first two years of the Plan. Besides work on Kathua Feeder of first 3 years of the Second Plan is equal to 70.6 % of the total plan pro- the Ravi Canal and Pratap Canal is progressing very satisfactorily and vision for these 3 years made in the budgets. Substantial results are expected by the end of the 2nd Plan.
Planning Department
Directorate of Information Jammu and Kashmir Government
Keywords: Introductory; Agriculture; Irrigation; Animal Husbandry; Co-Operation; Fisheries; Forestry Schemes; Soil Conservation; C. D. and n. E. Services; Power Projects; Industries; Welfare of Schedule Castes and Other Backward Classes; Rural and Urban Water Supply; Local Bodies; Statistical Schemes; Road Development